2018
DOI: 10.3390/w10080999
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Risk of Phthalate Ester (PAE) Contamination in Soils and Crops Irrigated with Treated Sewage Effluent

Abstract: Waste/reclaimed irrigation water has been promoted due to water shortages in arid and semi-arid areas. However, this process may be one of the sources of phthalate esters (PAEs) in agricultural soils, and the potential risks of PAEs for soil ecosystems and human health have attracted considerable attention. A two-year (from October 2014 to October 2016) field experiment was conducted to assess the contamination risk of PAEs from reclaimed irrigation water in winter wheat (Triticum aestivum L.) and summer maize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…3a and b ). 160 Often, there are seasonal variations in the deposition of phthalates in the soils. For instance, the concentration of phthalates in topsoils at winter wheat harvest was significantly higher than those at the summer maize harvest.…”
Section: Additives – Biphenyls/phthalatesmentioning
confidence: 99%
See 1 more Smart Citation
“…3a and b ). 160 Often, there are seasonal variations in the deposition of phthalates in the soils. For instance, the concentration of phthalates in topsoils at winter wheat harvest was significantly higher than those at the summer maize harvest.…”
Section: Additives – Biphenyls/phthalatesmentioning
confidence: 99%
“…For instance, the concentration of phthalates in topsoils at winter wheat harvest was significantly higher than those at the summer maize harvest. 160 Implications are that wet deposition scavenges the phthalates easily from their source materials, subscribing significantly to their transport into soil media. Phthalates can easily reach the agricultural soils by applying agricultural plastic films, irrigation water, sewage sludge, biosolids, and fertilizers.…”
Section: Additives – Biphenyls/phthalatesmentioning
confidence: 99%
“…Likewise, higher values of phthalates’ AF were observed in wheat and maize ( Tan et al 2018 ). In another study, AF was calculated for six phthalates in the grains of Triticum aestivum and Zea mays that were observed to vary from 0.33 to 33.75 ( Li et al, 2018b ). DBP has been reported to accumulate and translocate like other lipophilic pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…These scenarios are different from those that actually occur in the Mezquital Valley but are undoubtedly important references to consider in future research, which mainly concern factors that influence the transportation and observed destination of EDCs and analysis in soil, roots, leaves, and edible crops [55]. Yet, there are undoubtedly important references to consider in future research studies, which are mainly regarding the factors influencing the transport and observed destination of EDCs [56,57], in an analytical experience for detection in soil, roots, leaves, and part of the edible cultivation [52], as well as in the risk assessment associated with the presence of EDCs in crops in the region [49,58].…”
Section: Discussionmentioning
confidence: 99%
“…Phthalates have been extensively investigated in different agricultural areas of the world. They have been observed in soil and crops, and, in many cases, in concentrations within the acceptable limits of risk for human consumption [49]. Lastly, carbamazepine, which is among the extensive list of drugs reported in the literature, is possibly the most frequently studied due to its characteristics of persistence in the environment.…”
Section: Estimation On Human Health Risksmentioning
confidence: 99%